Dark Vibronic Polaritons and the Spectroscopy of Organic Microcavities - Herrera-Urbina, F (American Physical Society, 2017)
Organic microcavities are photonic nanostructures that strongly confine the electromagnetic field, allowing exotic quantum regimes of light-matter interaction with disordered organic semiconductors. The unambiguous interpretation of the spectra of organic microcavities has been a long-standing challenge due to several competing effects involving electrons, vibrations, and cavity photons. Here we present a theoretical framework that is able to describe the main spectroscopic features of organic microcavities consistently. We introduce a class of light-matter excitations called dark vibronic polaritons, which strongly emit but only weakly absorb light in the same frequency region of the bare electronic transition. A successful comparison with experimental data demonstrates the applicability of our theory. The proposed microscopic understanding of organic microcavities paves the way for the development of optoelectronic devices enhanced by quantum optics. © 2017 American Physical Society.